Development of instant coconut milk-based rice porridge with corn (ginataang mais) - Umali, Gelen Vestalez Co
ABSTRACT This study developed an acceptable instant coconut milk-based rice porridge with corn guinataang mais. The developed product ma have potential use as an instant snack commodity that will help answer the demand for more processed rice-based products and perhaps as a disaster food. The first phase of the study dealt with the selection of the most acceptable guinataang mais formulation. The formulation from Estrella (1987) was established as the most acceptable formulation and was described to be moderately cream in color, with slightly soft rice, moderately thick in consistency, with moderately distinct guinataang flavor. Modification was done to improve the sweetness of this guinataang mais formulation. The second phase of the study dealt with the selection of the best corn cultivar to be used in the standard formulation of guinataang mais. The 2 test cultivars used were waxy corn and yellow sweet corn. Sensory evaluation showed that yellow sweet corn was the more acceptable corn cultivar for the modified guinataang mais formulation from Estrella (1987). The instant guinataang mais was prepared by hydration, gelatinization, dehydration and putting of rice, preparation of instant corn, and compounding of the instant product. The instant rice was prepared by soaking in 0.5% calcium chloride solution at 50C for 30 min, cooking in steam under pressure at 15 psi and 121C for 6 min, drying in a by convection air drying at 55C for 55 min, and puffing in vegetable oil at 200C for 2 sec. Instant corn was prepared by initially blanching in boiling water for 3 min, soaking in 10% lye solution for 1 min, then drying by convection drying at 55C for 80 to 100 min. Sensory evaluation was done to determine the acceptability of the instant guinataang mais as compared to the standard formulation of guinataang mais prepared using the conventional mode of cooking. The rehydrated instant guinataang mais sample was described as cream in color, with slightly soft rice and corn, moderately thick consistency, slightly distinct aroma and slightly distinct flavor. As compared to the standard formulation of guinataang mais, the instant guinataang mais sample showed no significant difference in the overall acceptability of the samples at 5% level of significance. The instant guinataang mais product consisted of instant rice and corn, instant coconut powder, sugar, salr, and lambda-carrageenan. The compounded instant guinataang mais had a pH of 6.06, Aw of 0.61, TPC result of about 10^4 cfu/g and YMC result of <10 cfu/g. Upon rehydration, the guinataang mais sample had a pH of 6.75, Aw of 0.98, TPC of 10^4 cfu/g, and YMC of <10 cfu/g. The cost per 75 g dried serving portion (approximately 300 ml upon rehydration) was computed at P13.52 with a 10% mark-up. Recommendations for further studies included upscaling the production of the product to bench scale and pilot scale productions, and storage stability studies of the instant guinataang mais product.